Diffusivities and atomic mobilities in fcc Ni–Mo–Nb alloys: high-throughput experiments and calculations - Meifang Tang; Huixin Liu; Xiangyang Yin; Shiyi Wen; Yong Du (Journal of Materials Research and Technology)
The diffusion investigation of fcc Ni–Mo–Nb system is critical for establishing the kinetic database for the development of both Ni-based superalloys and cemented carbides, yet comprehensive diffusion studies remain absent. In this work, a total of twelve fcc Ni–Mo–Nb ternary diffusion couples were annealed at 1273, 1373, and 1473 K for 504, 336 and 120 h, respectively. The compositional profiles of these diffusion couples were determined using Electron Probe MicroAnalysis. Utilizing available thermodynamic and kinetic databases for the sub-binary systems of the fcc Ni–Mo–Nb system and the experimentally determined composition profiles, the assessments of interdiffusivities and atomic mobility parameters in fcc Ni–Mo–Nb alloys were simultaneously performed through a numerical inverse method incorporated in the CALTPP (CALculation of ThemoPhysical Properties) software. The good consistency between the simulated composition profiles by the numerical inverse method and the measured ones is further validated, demonstrating the reliability of the present assessments. Meanwhile, the model-predicted composition-dependent diffusivities indicate that the diffusion of Nb in fcc Ni is notably faster than that of Mo in fcc Ni. By utilizing the presently established atomic mobility parameters, the pre-frequency factor and activation energy were further predicted. It should be noted that the present diffusion investigation is pivotal for predicting microstructure evolutions and designing desired properties for advanced Ni-based superalloys and cemented carbides.